An Exploratory Study of Transferring From a Community College Into a 4-Year Music Education Program. Issue 2 (February 2023) - Koner, Karen; Eros, John
Two-year community colleges (CCs) provide access to higher education for those who might not otherwise have had the opportunity. Research into CCs has seen growth in past years, with a focus on areas of curriculum, such as music history and musicianship; however, research within music education regarding transfer students is remarkably slim. This qualitative case study investigated the experiences of four CC transfer students in music as they transitioned into music education programs at 4-year universities. The primary research question was: How do transfer students in music education describe their experiences making the transition from 2- to 4-year music programs? Current analysis indicates a need for greater communication between different institutions, the presence of transfer-specific systematic barriers for students, and the importance of community and support for transfer music education majors.